2020
DOI: 10.1002/eat.23395
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder pathology and compulsive exercise during the COVID‐19 public health emergency: Examining risk associated with COVID‐19 anxiety and intolerance of uncertainty

Abstract: Objective: COVID-19 has led to disruptions in daily living and increased uncertainty about physical, financial, social, and psychological consequences, which may contribute to anxiety, eating disorder (ED) pathology, and compulsive exercise. Individual factors, such as intolerance of uncertainty, may impact risk for ED pathology and CE in response to COVID-19 anxiety. The current study examined associations between COVID-19 anxiety, trait intolerance of uncertainty, and COVID-19 intolerance of uncertainty and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 32 publications
6
67
0
10
Order By: Relevance
“…However, it has been determined that in the COVID-19 pandemic, existing variables were investigated with different concepts. Studies have shown that there are positive relationships between intolerance of uncertainty and fear of COVID-19 (Duman, 2020), depression, anxiety and stress (Bakioğlu et al, 2020), eating disorders (Scharmer et al, 2020), obsessive-compulsive disorder (Wheaton et al, 2020), health anxiety (Tull et al, 2020) and loneliness (Parlapani et al, 2020). It was determined that there is a negative relationship between intolerance of uncertainty and spirituality and resilience (Kasapoğlu, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been determined that in the COVID-19 pandemic, existing variables were investigated with different concepts. Studies have shown that there are positive relationships between intolerance of uncertainty and fear of COVID-19 (Duman, 2020), depression, anxiety and stress (Bakioğlu et al, 2020), eating disorders (Scharmer et al, 2020), obsessive-compulsive disorder (Wheaton et al, 2020), health anxiety (Tull et al, 2020) and loneliness (Parlapani et al, 2020). It was determined that there is a negative relationship between intolerance of uncertainty and spirituality and resilience (Kasapoğlu, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be predicted that the power of moral outrage to affect intolerance of uncertainty will decrease with the effects of relational interdependence. When the literature is reviewed, during the COVID-19 pandemic period, intolerance of uncertainty (Bakioğlu et al, 2020;Duman, 2020;Kasapoğlu, 2020;Parlapani et al, 2020;Tull et al, 2020;Scharmer et al, 2020;Wheaton et al, 2020 ), moral outrage (Godshall, 2021;Neys et al, 2020;Davidson et al, 2020;Rushton & Thompson, 2020) and relational interdependence (Graupmann & Pfundmair, 2020) have all been the subject of studies. However, no studies have been found in which these concepts, which are thought to be related to each other, have actually been examined together.…”
Section: The Mediating Role Of Relational Interdependencementioning
confidence: 99%
“…While several studies suggest differential outcomes based on eating disorder (ED) type (e.g, anorexia nervosa vs binge eating), 6 persons with histories of (ED) may be particularly affected by pandemicrelated stressors, exacerbating risk for recurrence or elevated severity of their ED and worsening symptoms. [6][7][8][9][10][11][12] Preliminary studies examining disordered eating behaviors (DEB) during the COVID-19 pandemic cautioned how lockdown may exacerbate problematic eating behaviors, [13][14][15] and that ED may shape COVID-19 risk. 16 In an Italian community sample collected at two different phases of Italy's pandemic lockdown, Cecchetto et al 17 found that depression and anxiety were associated with emotional eating, and that stress was associated with binge eating.…”
Section: Disordered Eating Behavior Eating Disorders and Covid-19mentioning
confidence: 99%
“…En las pruebas científicas cuyo objeto de estudio consideró una población joven se observó, durante el confinamiento, que los adolescentes con TCA presentan una mayor reactivación de sus síntomas tanto compulsivos como restrictivos y afectivos, así como un aumento de riesgo de autolesión y suicidio que hace requerir más visitas para evitar un mayor riesgo de ingreso (15,16).…”
Section: Introductionunclassified